(untitled) (Research, Society and Development, 2021)
The bridges are important structures for the development of cities, they allow access to places previously isolated due to geological non-conformities or by obstacles such as rivers and valleys, facilitating the access of products and the movement of vehicles and people. The conservation, maintenance, and recovery of these structures are essential for their proper functioning and the safety of their users. However, it is not uncommon to find bridges out of their ideal state of use, presenting a lot of pathologies, and, for these pathologies to be repaired, it can be used various recovery techniques and kinds of treatments. This study aims to analyze the pathologies and their possible options of restorations on the bridge located at João Lopes da Silva Street, Manoel Pimenta neighborhood, in the city of Teófilo Otoni - Brazil. The identification and classification of the pathologies and nonconformities found in the artwork have been carried out. The analyzed bridge needs maintenance so that its functionality is not affected, requiring appropriated recovery techniques such as the use of epoxy resin in cracks, removal of corrosion from reinforcement and application of anticorrosive paints, scarification of concrete in the area in which there is disaggregation, and concreting through forms and drainage devices compatible with local needs, providing a longer life span and avoiding inconvenience for users.